Vole impact on tree regeneration: insights into forest management - Heroldová, M.; Homolka, M.; Tkadlec, E.; Kamler, J.; Suchomel, J.; Purchart, L.; Krojerová, J.; Barančeková, M.; Turek, K.; Baňař, M. (Julius Kühn-Institut, 2011)
In Europe, much of the damage to tree seedlings in plantations is caused by rodents, such as common vole (Microtus arvalis), field vole (M. agrestis) and bank vole (Myodes glareolus). To understand the relationships between the environmental variability which may influence the rodent impact in forest plantations we conducted a study in 12 forest regions of the Czech Republic. In total, we recorded cumulative damage in 19,650 young trees of 8 species at 393 plots. Broadleaves were far more affected by gnawing than conifers (mean 10% and 3%, respectively). Of the monitored species, beech was damaged most often (24% of individuals). The intensity of browsing differed between the regions (6- 60% of browsed individuals) with the lowest damage at altitudes below 400 m a.s.l. The proportion of the trees damaged increased with age of the plantation up to 6 years. The factors which principally influenced the impact on trees were herb layer plant cover, its height, its species composition, litter size and presence of weedy species.